Sistem Pendukung Keputusan Pemilihan Peserta Jamkesmas (Jaminan Kesehatan Masyarakat) Dengan Metode (Arras) Additive Ratio Assesment - T. Rezka Aditya Syahputra; Rivalri Kristianto Hondro; Kenedi Tampubolon (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The problem in the process of determining Jamkesmas candidates faced by the Pantai Labu Health Center still has several problems, such as the existence of subjectivity that tends to assess the Jamkesmas candidates still leads to personal opinions so that the assessment process takes quite a long time because it is done manually, resulting in the decision-assessment process. becomes slow and this is certainly not very good because it affects the smooth operation of the Pantai Labu Health Center. Therefore, to overcome the problems faced by the Pantai Labu health center, a decision support system is needed to select Jamkesmas candidates. When choosing a method, it is necessary to use the additive ratio assessment method (ARAS). The system will obtain a ranking decision based on each alternative choice based on a number of predetermined criteria. The alternative with the most weights is the recommended alternative. To realize the decision support system, a decision support system application program is designed. Designed using a website-based application that will be used with a multi-user concept, which is designed only for user convenience, through this decision support system application, it is expected to facilitate the process of determining Jamkesmas candidates, it is expected to get the best results from the Additive Ratio Assessment (ARAS) method. With the ARAS method, it is hoped that this research can provide assistance to the company in determining Jamkesmas candidates. As for the results of the Decision Support System in the process of determining the Jamkesmas candidate is Alternative A3 with a value of 1.0000 in the name of "Fajar Anugerah".